Experimental verification of Re-Fib method for recycling fibres from composites. (2nd January 2016) - Gong, Guan; Olofsson, Kurt; Nyström, Birgitha; Juntikka, Magdalena; Oxfall, Henrik; Lindqvist, Karin
Abstract: A new concept, Re - Fib, was developed within an EU project, REFORM, to recycle carbon and glass fibres from polymeric composite structures, aiming to reduce energy consumption and degradation of fibre properties during recycling. The optimized thermolysis treatment, 24 h at 380 °C, was verified able to recover clean fibres from most tested composite structures containing different thermoset resins (epoxy, vinyl ester, and polyester) and various core materials such as polyvinyl chloride (PVC), polyurethane (PU), and wood. Single-fibre test was performed in dynamic mechanical analysis (DMA). The reduction of strength was found around 26% for carbon fibres and 34–40% for glass fibres. Thermally recycled glass fibres were melt-compounded with recycled polypropylene (rPP); the resultant composites showed promising mechanical properties. Abstract :